FORMULASI DAN UJI KINERJA ASPHALTENE DISSOLVER DENGAN PENGGUNAAN SURFAKTAN ANIONIK DARI MINYAK SAWIT - Felga Zulfia Rasdiana, Erliza Hambali, dan Pudji Permadi (Jurnal Teknologi Industri Pertanian, 2017)
Asphaltene deposition is a major problem in petroleum industry causing slow production or even operational shutdown for removal of deposits. This research was conducted to obtain the best formulation of asphaltene dissolver to dissolve asphaltene deposits with the use of an palm oil anionic surfactant and to obtain performance information of asphaltene dissolver formula. The tested formulation were methyl ester sulfonate acid (MESA) and methyl ester sulfonate (MES), each with concentrations of 0%, 1%, 3%, and 5% in toluene mixed at a temperature of 40°C for 30 minutes. The best asphaltene dissolver produced was MESA 1% in toluene with the lowest interfacial tension (IFT) value of 3.95E-03 dyne/cm and solubility degree of 69.58%. Asphaltene dissolver produced showed a good performance in changing the wettability of rocks with an increase on contact angle of 48,6o to 80,89o, and  increase wettability on metal surface with asphaltene release of 99.32% as well as showed good performance on dispersion, desorption and filtration.Keywords : asphaltene, asphaltene dissolver, anionic surfactant, MESA, MES